MOTIVATION ANALYSIS ON CUSTOMER OF ISLAMIC MICROFINANCE INSTITUTION - Dhika Amalia Kurniawan; Muhammad Faris Irwanto (CAPITAL: Jurnal Ekonomi dan Manajemen, 2018)
In Ponorogo, one of microfinance institution developed by Pondok Modern Darussalam Gontor namely Baitul Mal Wat Tamwil La-Tansa Gontor. BMT La-Tansa Gontor has 2462 customers from various regions in Ponorogo. The high demand for financial services for the community, especially in Ponorogo makes the community more selective in choosing the financial institution that will be used, this is evidenced by the high motivation of customers to use the services of BMT La-Tansa Gontor Ponorogo.The purpose of this study is to analyze the customer motivation of using BMT La-Tansa Gontor services. This research used qualitative method with grounded theory. Data collection used observation techniques, interviews, and documentation. Determination of the sample used in this study using a purposive sampling, while data analysis method used is a method of miles and hubberman with internal and external motivation as an instrument. From this research, it can be concluded that the motivation on customer of BMT La-Tansa Gontor is caused by internal motivation; (1) Implement islamic principles; (2) Personal motivation; (3) Honest revenue sharing; and (4) Halal result. The factors from external motivation on BMT La Tansa Gontor customer (1) Service factor;(2) Influence of other; (3) Transparency factor, (4) Promotion factor; and (5) Transaction factor. From the results of this research, it is expected the service quality in BMT La-Tansa Gontor can be improved to build customer satisfaction, trust and loyalty. Researcher hopes to increase the socialization of BMT La-Tansa Gontor to the community to manage property according to Islamic principles.Keywords: BMT La-Tansa Gontor, Customer, External, Internal, Motivation